2022
DOI: 10.3390/foods11121697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Environmental Impacts from Different Perspectives—Case Study of Egg Value Chain System in Serbia

Abstract: The environmental performance of various aspects of animal origin food supply chains has been the focus of research in recent years, and has provided useful information. However, there were no studies that covered the entire egg supply chain from different perspectives. The aim of this study was to analyze the majority of environmental impacts in the table egg supply chain comprising of three subsystems: farms, retail outlets and households, with quantification of each individual subsystem and the entire suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The studies presented in Table 1 predominantly highlight the relevance of the LCA and identify that the feeding of laying hens and the proper management of manure are the main contributors to the emission of greenhouse gases and impact the life cycle of the eggs. It was also possible to identify that these studies did not include the complete life cycle from the cradle to the retail of the eggs, only up to the pre-gate of production [20,[43][44][45][46][47][48][49][50]. It should be noted that the most relevant impacts considered in the studies presented in Table 1 were: Acidification (kg SO 2 eq.…”
Section: Abín Et Al (2018) [60] Spainmentioning
confidence: 99%
“…The studies presented in Table 1 predominantly highlight the relevance of the LCA and identify that the feeding of laying hens and the proper management of manure are the main contributors to the emission of greenhouse gases and impact the life cycle of the eggs. It was also possible to identify that these studies did not include the complete life cycle from the cradle to the retail of the eggs, only up to the pre-gate of production [20,[43][44][45][46][47][48][49][50]. It should be noted that the most relevant impacts considered in the studies presented in Table 1 were: Acidification (kg SO 2 eq.…”
Section: Abín Et Al (2018) [60] Spainmentioning
confidence: 99%
“…Indicators of Specific Products: The Egg Supply Chain Mitrovic et al [98] analyzed the egg supply chain to comprehend the environmental impacts by observing a sample of three main categories of actors of the chain: farmers, retailers, and householders. The results revealed that the greatest environmental impacts came from the production of feed for laying hens and the use of natural resources.…”
Section: Indicators Of Short and Long Food Supply Chainsmentioning
confidence: 99%
“…Figure 1 illustrates the egg supply chain, as presented by Bux and Amicarelli [30], Pelletier et al [31,32] and Mitrovic et al [33]. The egg supply chain starts with breeder flock facilities, which provide eggs to hatcheries, which are then placed into incubators for a total of 21 days.…”
Section: Textual Analysis 231 Egg Supply Chain Characteristics Under ...mentioning
confidence: 99%